Answer:
[tex]\dfrac{dy}{dx}\left ( \dfrac{x^2+y^2}{2\times y}-y \right )=x[/tex]
Step-by-step explanation:
Given that
[tex]x^2+y^2=2cy----(1)[/tex]
Now by differentiating the above equation with respect to x
[tex]2\times x+2\times y\times \dfrac{dy}{dx}=2\times c\times \dfrac{dy}{dx}[/tex]
[tex]x+ y\times \dfrac{dy}{dx}= c\times \dfrac{dy}{dx}-----(2)[/tex]
Form the above equation (1)
[tex]c=\dfrac{x^2+y^2}{2\times y}[/tex]
Putting the value of c in the equation (2)
[tex]x+ y\times \dfrac{dy}{dx}= \dfrac{x^2+y^2}{2\times y}\times \dfrac{dy}{dx}\\\dfrac{dy}{dx}\left ( \dfrac{x^2+y^2}{2\times y}-y \right )=x[/tex]
Thus the differential equation of the given curve will be
[tex]\dfrac{dy}{dx}\left ( \dfrac{x^2+y^2}{2\times y}-y \right )=x[/tex]
Curve for different value of c :
x² +y² = 2 c y
The above equation is an equation of a circle.That circle is having center on the y-axis.